Pancreaticopericardial Fistula: A Case Report and Literature Review - Muhammad S. Khan; Najmi Shahbaz; Hassaan A. Zia; Muhammad Hamza; Henna Iqbal; Ahmed Awab (Case Reports in Critical Care)
Purpose. Pancreaticopericardial fistula (PPF) is an extremely rare complication of acute or chronic pancreatitis. This paper presents a rare case of PPF and provides systematic review of existing cases from 1970 to 2014. Methods. A PubMed search using key words was performed for all the cases of PPF from January 1970 to December 2014. Fourteen cases were included in the study. The cases were reviewed for demographic characteristics, diagnostic modalities, and treatment. Descriptive analysis of these variables was performed. Results. Median age was 43 years. 78% were known alcoholics and 73.3% had chronic pancreatitis. Dyspnea was present in 78%. Cardiac tamponade was present in 53%; 75% of patients had known chronic pancreatitis (RR = 0.74). Surgery was associated with best treatment outcomes and 50% of patients who underwent endoscopic treatment survived. Conclusion. PPF is a rare disease. This paper indicates that acute cardiac tamponade in patients with history of alcoholism and chronic pancreatitis could be a sign of an existing pancreaticopericardial fistula and early surgical intervention could be life-saving.